PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, MOTIVASI KERJA TERHADAP DISIPLIN KARYAWAN PADA PT KHARISMA PEMASARAN BERSAMA NUSANTARA (KPBN) BELAWAN - mala, Nurmala (MTU PRESS, 2023)
Both formal and informal units need a personal leader who encourages his subordinates to be productive because the spirit of a leader in an organization is absolutely absolute to be a role model for his subordinates. A dynamic and effective manager is the most basic resource encountered, therefore every leader must understand leadership theory by knowing the talent or potential possessed by his subordinates or owned by himself. Leadership is the most important part of management, this is because leadership is the driving force for the creation of optimization of production factors (human, capital, or methods) in an organization or organization. The approach in this study uses an associative and quantitative approach. The associative approach is an approach where to find out that there is a relationship or influence between the second variable (the independent variable and the independent variable). Quantitative approach is a method that is more on the aspect of measuring objectively on the data or formulas obtained. The results showed that there was a significant influence between leadership style and work environment on discipline.